The challenges of home-based learning in Covid-19 season: An overview of rural school in Sabah, Malaysia - Gurumoorthy Poobalan; Junaidi Asman; Roslee Talip; Rosna Padan; Zulhairul Ramlee; Sukuneswari Kaliappan (Human Resource Management Academic Research Society, 2021)
The COVID-19 epidemic has spread throughout the country, affecting nearly every area, including the education sector. Since the adoption of the Movement Control Order (MCO) on March 18, 2020, home-based learning has been widely implemented across the country for quite some time. The purpose of this study is to assess the problems that students faced while learning at home during the COVID-19 academic season. This research was carried out at a rural school in the Sabah district of Beluran. Pupils in Forms 4 and 5 (a total of 178 students) were involved in this study. The survey was carried out through the use of a Google form, which was sent to students through social media. According to the findings of the survey, students experience a total of 18 challenges when it comes to completing their homework and performing their homework assignments at home. The students themselves have also contributed some tips for tackling the difficulties associated with home-based learning. We expect that the findings of this study will serve as a guide for teachers, schools, district education office management, the State Education Department, and the Ministry of Education Malaysia in developing policies and coordinating the implementation of home-based learning programs in the future.